Optimizing the Use of Solid-Phase Reversible Immobilization Beads for High-Throughput Full-Length 16S rDNA Sequencing Library Construction - Yinmei Li; Ziqiang He; Mimi Kong; Dong Jin (Zoonoses)
Solid-phase reversible immobilization (SPRI) beads are widely used for high-throughput sequencing library construction to purify and recover nucleic acids. This research was aimed at investigating the effects of SPRI bead ratio, incubation time, and elution time on nucleic acid recovery during full-length 16S rDNA high-throughput sequencing library construction. The effects of different SPRI bead ratios, incubation times, and elution times were compared for three different initial sample amounts. An L9(3 3 ) orthogonal experiment was designed to determine the optimal combination of these factors. The incubation time of three factors including SPRI beads ratio, incubation time, and elution time had a statistically significant effect on the recovery rate for the initial sample amount of 1500 ng and 3000 ng. The orthogonal experiment results indicated that incubation time had the greatest impact among the three factors. Incubation time significantly influences recovery rate in full-length 16S rDNA high-throughput sequencing library construction. The use of 0.8× SPRI beads, 15 minutes of incubation, and 10 minutes of elution resulted in the highest recovery rate. SPRI beads offer a viable method for recovering full-length 16S rDNA amplicons.